Chemical and spectroscopic studies of chromone derivatives - Ramaite, Ipfani David Isaiah (Rhodes University, Faculty of Science, Department of Chemistry, 1993)
A number of biologically active chromones occur in plants (eg. Khellin) and research in this field has eventually led to the discovery of chromoglycic acid, which is widely used as a sodium salt in asthma therapy. Since biological activity may be related to acidity, a range of chromone-2-carboxylic acids have been prepared via Claisen acylation of substituted o- hydroxyacetophenones and their acid dissociation constants determined potentiometrically to explore substituent effects. From this study it has been found that introduction of certain groups does have a marked effect on acidity. A variety of acrylamide derivatives have been prepared via the dimethylamine-mediated ring opening of chromone-2-carboxamides which, in turn, were prepared from the chromone-2- carboxylic acids via the corresponding acid chlorides. Variable temperature NMR spectroscopy was employed to examine the effect of substituents on the rotational barriers and it has been found that for the acrylamides examined, ring substituents have little effect on the rotational barriers. A combination of low resolution, high resolution and meta-stable peak analysis has been used to study mass fragmentation patterns for a series of acrylamide derivatives. The proposed fragmentation pathways for selected peaks have been found to be common to all the spectra examined when differences in the atomic masses of substituents were taken into account.
Keywords: Heterocyclic compounds -- Derivatives -- Research; Benzopyrans -- Research; Coumarins -- Research